Emission of greenhouse gases in the soil under the green manure effect - Sosa-Rodrigues, Breno Augusto; García-Vivas, Yuly Samantha (Agronomía Mesoamericana, 2019)
Introduction. Soil management practices in agroecosystems, such as the use of green manures (GM), positively affect greenhouse gas (GHG) emissions. Objective. The objective of the research was to evaluate CO2,CH4, and N2O emission of a soil cultivated with corn and soybean under the use of green fertilizers, fallow (B), and nitrogen fertilization. Materials and methods. Between July 2011 and June 2012, in a Typic Haplustert located in Valle del Cauca, Colombia, corn and soybeans were planted in a intervleaved manner, and the monocultures of corn and soybeans were managed in a conventional manner. The association between Mucuna pruriens var. utilis and maize was established as GM, ninety days after sowing, the total residues were incorporated as GM or disposed on the soil surface as organic mulch (AO). Eleven treatments were used under the design of randomized complete blocks, with 32 + 2 factorial arrangement, with three repetitions. The main plots were GM, AO and B. Each was divided into sub-plots corresponding to compost fertilization, industrial chemical synthesis fertilizer and no additions. In the flowering and grain filling stage of the crops, variables such as N2O, CH4, CO2 and total water-filled porosity were analyzed. Results. CO2 flow was higher in the intercrops added with GM/AO compared to monocultures. In the main plots, the use of industrial chemical synthesis fertilizers significantly stimulated N2O and CH4 fluxes. Conclusion. The use of high quality organic materials such as GM/AO did not ensure GHG sink soils in the short-term, since soil conditions and nitrogen fertilization significantly influenced emissions.